2021
DOI: 10.25259/sni_730_2021
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of Streptococcus anginosus infectious intracranial aneurysm: Proper management of a poor prognosis

Abstract: Background: Infectious intracranial aneurysms (IIAs), sometimes referred to as cerebral mycotic aneurysms, are an uncommon but feared compilation of bacterial endocarditis, occurring in up to 5% of all bacterial endocarditis cases. While IIAs carry a low risk of rupture, a ruptured mycotic aneurysm carries devastating neurologic consequences with up to an 80% mortality rate secondary to subarachnoid and intracerebral hemorrhage. Case Description: A 69-year-old man undergoing antibacterial therapy for Strep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Co-morbidities of group C are primarily detected in women. Specifically, they are diseases like Streptococcal pharyngitis (ICD J02.0) 11 , 12 , chronic obstructive pulmonary disease (ICD J44.8) 13 , hypothyroidism (ICD E03.9) 14 , 15 and panic disorder (ICD F41.0). In men, group C comorbidity is limited to depression (ICD F32.9).…”
Section: Discussionmentioning
confidence: 99%
“…Co-morbidities of group C are primarily detected in women. Specifically, they are diseases like Streptococcal pharyngitis (ICD J02.0) 11 , 12 , chronic obstructive pulmonary disease (ICD J44.8) 13 , hypothyroidism (ICD E03.9) 14 , 15 and panic disorder (ICD F41.0). In men, group C comorbidity is limited to depression (ICD F32.9).…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the pooled cohort of patients from the literature revealed that 65% of patients with IIAs presented with bacterial IE ( 5 ). In the pre-antibiotic era, this ratio commonly arises in patients with prosthetic valves, nosocomial-acquired blood stream infections, or a history of intravenous drug use ( 6 , 7 ). Less commonly, IIA can also result from the direct extension of intracranial bacterial infections, such as meningitis, cavernous sinus thrombophlebitis and orbital cellulitis, often in patients who are immunosuppressed ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…The terminology «mycotic aneurysm» was used for the first time by William Osler in Gulstonian Lectures of 1885, it refers to a dilatation of an arterial wall caused by any infectious etiology [2]. It is a serious clinical condition that carries a significant morbidity with up to 80% mortality rates when reptured [3]. Therefore, an early and rapid diagnosis is critical for timely treatment to optimize patient outcome.…”
Section: Austin Journal Of Radiologymentioning
confidence: 99%